3D printing of fiber reinforced soft robotics - Yap, Yee Ling (2018)
Soft robotics is a rapidly growing new field of robotics whereby the robots are fundamentally soft and elastically deformable. Many of the soft robotics are inspired by soft bodied animals, are made of intrinsically soft, extensible and highly compliant materials. In this paper, 3D inkjet-printed fiber reinforced soft composites were used to develop a pneumatic actuated soft robotics. The fiber reinforced soft composites are able to remain flexible yet strong due to the thin inextensible fibers embedded within the matrix. Then it is being adopted into designing a soft robotic which can perform controlled motion such as extension with varying air pressure. The potential and challenges of current 3D printed soft robotics will also be discussed.